(untitled) (Modern education and development, 2025)
In the digital era, university students need to develop not only their professional competencies but also their digital literacy to meet the demands of the modern workforce. This research examines the methodological foundations of integrating digital skills into higher education curricula, ensuring that students acquire both subject-specific expertise and technological proficiency. The study explores the role of digital learning tools, artificial intelligence, and interactive educational environments in enhancing students’ professional growth. The research emphasizes the need for innovative teaching strategies that align with contemporary technological advancements, equipping future professionals with the necessary skills to thrive in a rapidly evolving job market.